2019
DOI: 10.3889/oamjms.2019.029
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Malondialdehyde and Nerve Growth Factor Serum Level with Diabetic Peripheral Neuropathy Score

Abstract: AIM:This study was conducted to identify malondialdehyde (MDA) serum level, nerve growth factor (NGF) serum level, diabetic peripheral neuropathy score and the correlation between MDA and NGF serum level with diabetic peripheral neuropathy score.METHODS:A cross-sectional study was conducted to observe diabetic patients in the internal medicine department in Dr M. Djamil Hospital, Padang, Indonesia. The MDA serum level was measured using Beuge method with thiobarbituric acid. The NGF serum level was analysed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It has been reported that the increased level of IL-6 in the placenta of GDM patients is caused by oxidative stress and inflammatory changes caused by hyperglycemia (24). MDA is one of the most reliable indicators of oxidative stress, and the increase of MDA level in diabetic patients is caused by the peroxidative decomposition of phospholipids caused by free oxygen radicals (29).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the increased level of IL-6 in the placenta of GDM patients is caused by oxidative stress and inflammatory changes caused by hyperglycemia (24). MDA is one of the most reliable indicators of oxidative stress, and the increase of MDA level in diabetic patients is caused by the peroxidative decomposition of phospholipids caused by free oxygen radicals (29).…”
Section: Discussionmentioning
confidence: 99%
“…A 33-year-old woman with a diagnosis of diabetic ketoacidosis, LADA, and sepsis caused by bronchopneumonia was treated. The problem with this patient is whether this patient is type 2 DM or another type of DM, given that clinically type 2 DM and other types of DM can be found in young adults [3], [4].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of LADA are similar to Type 1 diabetes but are found in adulthood. The slow progression of pancreatic β cell damage in LADA is initially almost always diagnosed as type 2 diabetes mellitus [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…NGF plays a key role in the neuronal development and function of both central and peripheral nervous system [ 62 ]. Lower concentrations of NGF are connected to reduced values of nerve conduction velocity, which is a fundamental player of the pathogenesis of DP [ 63 ].…”
Section: C-reactive Proteinmentioning
confidence: 99%